2015
DOI: 10.1371/journal.pone.0139625
|View full text |Cite
|
Sign up to set email alerts
|

mPneumonia: Development of an Innovative mHealth Application for Diagnosing and Treating Childhood Pneumonia and Other Childhood Illnesses in Low-Resource Settings

Abstract: Pneumonia is the leading infectious cause of death in children worldwide. Each year, pneumonia kills an estimated 935,000 children under five years of age, with most of these deaths occurring in developing countries. The current approach for pneumonia diagnosis in low-resource settings—using the World Health Organization Integrated Management of Childhood Illness (IMCI) paper-based protocols and relying on a health care provider’s ability to manually count respiratory rate—has proven inadequate. Furthermore, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 19 publications
1
82
0
Order By: Relevance
“…However, several health center-based CHNs were less motivated to enter data when the reports were not generated. These findings align with other research studies that have found technical issues such as screen freezes and delayed uploads impede efficient use and limit user uptake of mobile health applications [27, 55, 67]. A lower threshold of data completeness and accuracy for receiving automated reports may have improved usability.…”
Section: Discussionsupporting
confidence: 86%
“…However, several health center-based CHNs were less motivated to enter data when the reports were not generated. These findings align with other research studies that have found technical issues such as screen freezes and delayed uploads impede efficient use and limit user uptake of mobile health applications [27, 55, 67]. A lower threshold of data completeness and accuracy for receiving automated reports may have improved usability.…”
Section: Discussionsupporting
confidence: 86%
“…Updates to the mPneumonia application from the initial prototype reduced the time it took HCPs to complete the application the first time, cutting it by over 40% from a mean of 43.4 minutes (previously reported) to a median of 25 minutes (reported here). [23] Additional improvements to the application were also made based on the pilot test results.…”
Section: Discussionmentioning
confidence: 99%
“…The five questions used were identical to those from the prior field testing stage of the mPneumonia prototype. [23]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have concentrated their efforts in improving their interventions prior to evaluating the acceptability (23,24) and others investigated the acceptability of mHealth interventions demonstrating positive results (25)(26)(27)(28). Each of these studies evaluated interventions other than smartphone applications, such as short messaging service (SMS), telecommunication interfaces as well as ehealth interventions emphasizing protocol compliance and treatment adherence respectively.…”
Section: Previous Mhealth Interventionsmentioning
confidence: 99%